Einleitung: ‚Sieben weisen Meister‘ als globale Erzähltradition - Bildhauer, Bettina; Eming, Jutta; Schmidt, Nora (Das Mittelalter, 2023)
This introduction describes the exceptionally broad multilingual transmission and transcultural significance of ‘The Seven Sages of Rome’ in the mediaeval and early modern Middle East, Europe and Western Asia, also known under names such as ‘Dolopathos’ or ‘The Book / Tales of Sindbad / Sindibad / Syntipas / Sendebar’. We propose to approach this text as a multilingual tradition rather than one separated into different national philologies. The plot reports a non-consensual sexual encounter between a male and a female character, which raises issues of gender and of the wisdom needed to discern the ‘truth’ about this encounter as particularly important topics in the text. We also identify the flexible genre and narrative form of this text, which features multiple embedded narratives within the plot, as research priorities. Several contributions to this special issue have made advances in these areas, but this introduction also aims to identify further research questions that promise to yield additional important results for the premodern and early modern history of gender and literature. Scholars interested in pursuing this research in our emerging ‘Seven Sages’ network are invited to contact the authors. Keywords: Seven Sages of Rome; Book of Syntipas; Sindbād-nameh; Mishle Sendebar; Dolopathos
Gesehen am 13.07.2023